RISK FACTORS AFFECTING THE OCCURRENCE OF DIABETES MELLITUS (TYPE 2) AT SULTAN ISKANDAR MUDA HOSPITAL NAGAN RAYA DISTRICT - Desi Susila Wati; Susy Sriwahyuni (RADJA PUBLIKA, 2023)
Diabetes Mellitus (type 2) is a metabolic disease characterized by an increase in blood sugar levels caused by a decrease in insulin secretion or impaired insulin function. The aim of the study was to determine the risk factors that influence the incidence of type 2 diabetes mellitus at the Sultan Iskandar Muda Hospital, Nagan Raya Regency. The method used is quantitative with a cross-sectional research design. The sample in the study was 77 people using a purposive sampling technique. The research instrument uses a questionnaire sheet. The research analysis used univariate and bivariate analysis with the chi square test. The results of the study based on bivariate analysis found that there was a relationship between age (p-value=0.000), hypertension status (p-value=0.043), obesity status (p-value=0.019), consumption of risky foods: sweet foods (p-value= 0.039), sweet drinks (p-value=0.003), fatty/cholesterol foods (p-value=0.002), seasonings (p-value=0.016), fast food (p-value=0.002) , physical activity (p-value=0.023), and there was no relationship between gender (p-value=0.102), family history (p-value=0.364) and the incidence of type 2 diabetes mellitus. This study found that age, sex, family history, hypertension status, obesity status, consumption of risky foods and physical activity are risk factors that influence the incidence of type 2 diabetes mellitus. Suggestions, it is expected that type 2 .